DAMPAK PROGRAM BANTUAN SARANA PRODUKSI PERTANIAN TERHADAP PENDAPATAN PETANI CABAI DI DESA KAUNERAN KECAMATAN SONDER - Ariyano Alfa Randi Siwu; Juliana Ruth Mandei; Eyverson ., Ruauw (AGRI-SOSIOEKONOMI, 2018)
This study aims to determine how the impact of the Agricultural Production Facility Assistance Program on Chili Farmers' Income in Kauneran Village, Sonder District. Data collection is conducted from March to May 2018. The selection of farmer groups is done purposefully, namely the recipient farmer groups. This study uses primary data and secondary data. Primary data is obtained from direct interviews with respondents based on a list of questions (questionnaires) that have been prepared in advance and observations. Interviews were conducted on 20 respondents, namely all Kalelon group members as a recipient group of aid programs. Secondary data obtained through the internet by using google searching to access scientific journal articles and thesis from other universities has to do with the topic of this research which is about the impact of aid programs. The results showed that there were significant income differences, based on the t-test, between before and after receiving the aid program where the income of farmers after receiving assistance was greater than before receiving their assistance. The conclusion of this study is that the aid program has a positive impact because it increases farmers' income. *er+eprm*